2012
DOI: 10.5402/2012/103472
|View full text |Cite
|
Sign up to set email alerts
|

The Malnutrition of Obesity: Micronutrient Deficiencies That Promote Diabetes

Abstract: Obesity and diabetes are increasing in prevalence worldwide. Despite excessive dietary consumption, obese individuals have high rates of micronutrient deficiencies. Deficiencies of specific vitamins and minerals that play important roles in glucose metabolism and insulin signaling pathways may contribute to the development of diabetes in the obese population. This paper reviews the current evidence supporting this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
140
3
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(154 citation statements)
references
References 95 publications
4
140
3
7
Order By: Relevance
“…Furthermore, a comparison of Zn, Cr, Mn, and Mg concentrations in hair between the groups with BMI <25 and BMI >30 showed significant differences, with P less than 0.05 at least. The present results corroborate with those in previous studies (30)(31)(32).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, a comparison of Zn, Cr, Mn, and Mg concentrations in hair between the groups with BMI <25 and BMI >30 showed significant differences, with P less than 0.05 at least. The present results corroborate with those in previous studies (30)(31)(32).…”
Section: Discussionsupporting
confidence: 94%
“…Landmark clinical trials on lifestyle changes in subjects with prediabetes have shown that diet and exercise leading to weight loss consistently reduce the incidence of DM. Reducing excess weight and obesity is the key factor in managing DM more efficiently so that the overall health and general sense of well-being can be improved (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…Obese patients who have a high caloric intake of nutritionally deficient foods may also be malnournished [15][16][17]. The complication rate in malnourished obese patients was over 10%, which was three times higher than in obese patients with normal nutrition.…”
Section: Discussionmentioning
confidence: 98%
“…Malnutrition should be considered in obese patients who are a growing demographic in developed countries and with a proportional increase in TJA [15,17,31,32]. Obese patients who have a high caloric intake of nutritionally deficient foods may also be malnournished [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…To define malnutrition, most surgeons use serum laboratory values such as albumin concentration and total lymphocyte count. Obese patients are known to have micronutrient deficiencies such as iron and 25-hydroxy vitamin D [11,15,30], but the prevalence and significance of protein malnutrition in obese and non-obese patients undergoing TKA are not well characterized. Furthermore, it is unclear whether obesity and malnutrition are independently associated with adverse perioperative events.…”
Section: Introductionmentioning
confidence: 99%